Information technologies in the education of contemporary China: reality and opportunities - Wei, Sun (Filosofiya osvity. Philosophy of Education, 2023)
With the rapid development of modern information technologies, their integration into all areas of education is accelerating, which contributes to the penetration of innovations into the education space. The author emphasizes that the design of many educational technologies was focused on the goals of education and included a sufficient number of educational concepts and elements. However, if teachers blindly adhere to the traditional concept of “technology is only a tool”, then this creates a sense of superiority of their own status and a narrow understanding of the value of technology. The author relies in his research on the latest achievements in the field of not only high technologies that are used in education, but also on psychological and social research on the impact of the latter both on education and on a person. The author proposes to perceive technologies in the context of a new culture, and shows possible ways of their more adequate use. Working with artificial technological objects is not only the acceptance of an artificial object, but also the adoption of a technical culture, which indicates a new cultural relationship between people and technology, and vice versa. On the basis of analyzing the phenomenon and essence of contemporary information technology, the author of this article tries to find out the problems existing in the application of contemporary information technology in education through a questionnaire survey, and reflects on the influence of technology on teachers and students in the education system. The answers of the survey participants made it possible to present a picture of the use of information technologies in education as a holistic and complex process. The analysis of the results obtained, as well as everyday practical training in the skills of using high technologies, enabled the author to establish that the influence of information technologies on education is complex, this is a new stage in the development of education as a whole, which allows us to characterize the process of their use as a holistic system. The influence of technology has completely changed all structures and all participants in education. The results of the survey also made it possible to identify a number of problems that indicate shortcomings in the modern space of education, the didactic nature of learning in the sense of conveying and receiving information in new conditions (we are talking not only about digitalization as a process, but also about changes aimed at transforming teaching methodology).